EVALUATION OF PERFORMANCE AND TURNOVER OF HIGH GRADED HOTELS IN HYDERABAD - Sharma, Ashish; Khurana, Gaurav (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we will look at how hotels in Hyderabad can improve their performance and turnover. Among the main six business sectors in the country, Hyderabad drove the diagrams as far as development in normal inhabitance rate (AOR) in lodgings during Q3 2021. (July- September). As indicated by JLL’s examination, the city had the biggest inhabitance ascend in Q3 2021, with a 33.6 percent expansion over a similar quarter last year, surpassing Goa with 29.8%, Mumbai with 29.4%, Hyderabad with 26.8%, Delhi with 25.5 percent, and Chennai with 24.1 percent. Hyderabad was likewise positioned third in the country as far as income per accessible room development (RevPAR). In Q3 2021, Goa reappeared as the RevPAR pioneer, with a 389.8 percent gain over the low base of Q3 2020, trailed by Bengaluru with a 213.2 percent increment and Hyderabad with a 173.5 percent increment over a similar period the earlier year.